On the role of CoO in CoOx/TiO2 for the photocatalytic hydrogen production from water in the presence of glycerol. (2nd October 2015) - Khan, M.A.; Al-Oufi, M.; Tossef, A.; Al-Salik, Y.; Idriss, H.
Abstract: The photocatalytic water splitting activity of nanocomposite photocatalysts of TiO2 with CoOx was studied under UV and visible light, and the catalysts were characterized by XRD, XPS, and UV–vis techniques. The presence of CoOx enhances the hydrogen production activity of TiO2 by five times at an optimal loading of .2 wt. %. To investigate the role of CoOx, the photocatalytic activity was also studied under visible light and with different amounts of sacrificial agent. Our results indicate that the increasing activity was not due to increasing absorption of the visible light but most likely due to the role of CoOx nanoparticles as hole scavengers at the interface with TiO2 . XPS Co2p analyses of CoO/TiO2 showed a considerable decrease in their signal after prolonged reaction time (44 h) when compared to that of the fresh catalyst. Because part of Co 2+ cations is dissolved in solution, in neutral or acidic pH, the possible increase in the reaction rate upon their addition to TiO2 under UV excitation was investigated. No change in the reaction rate was observed upon, on purpose, addition Co 2+ cations to TiO2 under UV excitation. Thus, one may rule out the reduction of Co 2+ to Co 0 with excited electrons within TiO2 . In order to further increase the reaction rate, we have synthesized and tested a hybrid system composed of CoO and Pd nanoparticles (Pd wt. % = 0.1, 0.3, 0.5, and 1 wt. %) where 0.3 wt. % Pd – 2 wt. % CoO/TiO2 showed the highest rate. Abstract :